Kondisi Sosial Ekonomi Masyarakat Nelayan di Pantai Labuhan Jukung Krui Pasca Terbentuknya Kabupaten Pesisir Barat - Endri Yunita; Pargito Pargito; Risma Margaretha Sinaga (Faculty of Teacher Training and Education, University of Lampung, 2018)
This research purposes to reveal the socio-economic conditions in fishing communities located on Labuhan Jukung beach. This research is a qualitative research with ethnographic approach using data collection techniques through interviews, observation, and documentation. The results of the study showed that the results of research did not significantly change the socio-economic life of fishermen. The indicator can be seen from; Low human resources due to the low education of fishing communities, Low income levels due to lack of capital to buy fishing equipment that will affect productivity, Low health awareness, Fishermen's life patterns that look consumptive, Policy the government has not been right on target, The socio-economic situation of the community has resulted in disruption of work stability and the progress of the division region, the research of the socio-economic conditions of fishermen communities in Labuhan Jukung Beach after the expansion has not significantly progressed with the conditions at the time of expansion because government programs based on the vision and mission of division have not touched the lives of fishermen resulting in structural poverty in the community.Penelitian ini bertujuan untuk mengungkapkan kondisi sosial ekonomi di masyarakat nelayan yang berada di pantai Labuhan Jukung. Penelitian ini adalah penelitian kualitatif dengan pendekatan ethnografi menggunakan teknik pengumpulan data melalui metode wawancara, observasi,dan dokumentasi. Hasil penelitian menunjukkan bahwa hasil pasca pemekaran tidak mengubah secara signifika kehidupan social ekonomi nelayan. Indikatornya dapat dilihat dari; Sumber daya manusia rendah karena pendidikan masyarakat nelayan yang rendah,Tingkat pendapatan rendah karena kekurangan modal untuk membeli peralatan tangkap yang akan mempengaruhi produktivitas, Kesadaran terhadap kesehatan rendah,Pola hidup nelayan yang seperti terlihat konsumtif, Kebijakan pemerintah yang belum tepat sasaran, Keadaan sosial ekonomi masyarakat yang demikian mengakibatkan terganggunya stabilitas kerja dan kemajuan daerah pasca pemekaran sehingga menimbulkan kemiskinan struktural.Kata Kunci : Sosial Ekonomi, Masyarakat Nelayan, Kemiskinan Struktural.